2016
DOI: 10.1002/ange.201604594
|View full text |Cite
|
Sign up to set email alerts
|

From Gold Nanoseeds to Nanorods: The Microscopic Origin of the Anisotropic Growth

Abstract: Directly manipulating and controlling the size and shape of metal nanoparticles is ak ey step for their tailored applications.I nt his work, molecular dynamics simulations were applied to understand the microscopic origin of the asymmetric growth mechanism in gold nanorods.D ifferent factors influencing the growth were selectively included in the models to unravel the role of the surfactants and ions.I nt he early stage of the growth, when the seed is only af ew nanometers large,adramatic symmetry breaking occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The preservation of these metastable facets, however, has long been poorly understood. Recent computational modeling suggests that the coverage density of CTA + on {110} (1.49 molecules/nm 2 ) is identical to that on {100} (1.49 molecules/nm 2 ) and higher than that on {111} (1.31 molecules/nm 2 ) . As such, stabilizing these facets may have led to the extension of {110} facets on side surfaces of AuNRs.…”
Section: Monometallic Systemsmentioning
confidence: 99%
“…The preservation of these metastable facets, however, has long been poorly understood. Recent computational modeling suggests that the coverage density of CTA + on {110} (1.49 molecules/nm 2 ) is identical to that on {100} (1.49 molecules/nm 2 ) and higher than that on {111} (1.31 molecules/nm 2 ) . As such, stabilizing these facets may have led to the extension of {110} facets on side surfaces of AuNRs.…”
Section: Monometallic Systemsmentioning
confidence: 99%
“…Interestingly, the identified distribution of citrates over gold NR facets and their role in the anisotropic dissolution is very similar to the identified distribution of surfactants and their role in the anisotropic growth phenomena. Indeed, using molecular dynamic simulations, Sulpizi et al 28 have identified the role of surfactant layer that preferentially covers the (100) and (110) facets, leaving the (111) facets unprotected. This inhomogenous surfactant layer promotes anisotropic growth with the less protected tips growing faster, which explains the shape of NRs.…”
Section: Why the Ends Of Nanorods Are More Reactive?mentioning
confidence: 99%
“…Moreover, many MD works focused on the interaction between surfactants and metal surfaces have been performed to explain the growth of anisotropic nanostructures coated with ligands such as citrate, piptide, CTAB …. [28][29][30][31] However, to our knowledge such theoretical approaches have never been used to reveal the effect of surface functionalization on the dissolution processes of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In deposition and dissolution reactions, adsorbates can act as intermediates, site blocking spectators, and/or structure-altering mediators of reactivity. Adsorbate guided dissolution can be applied to etch highly anisotropic structures, but similar reaction conditions can lead to undesired effects, such as localized corrosion. , Likewise, adsorbates impact additive processes such as nanoparticle synthesis and the fabrication of multiscale microelectronic interconnects …”
Section: Introductionmentioning
confidence: 99%